MLL targets SET domain methyltransferase activity to Hox gene promoters. - Milne, T; Briggs, S; Brock, H; Martin, M; Gibbs, D; Allis, C; Hess, J (2002)
MLL, the human homolog of Drosophila trithorax, maintains Hox gene expression in mammalian embryos and is rearranged in human leukemias resulting in Hox gene deregulation. How MLL or MLL fusion proteins regulate gene expression remains obscure. We show that MLL regulates target Hox gene expression through direct binding to promoter sequences. We further show that the MLL SET domain is a histone H3 lysine 4-specific methyltransferase whose activity is stimulated with acetylated H3 peptides. This methylase activity is associated with Hox gene activation and H3 (Lys4) methylation at cis-regulatory sequences in vivo. A leukemogenic MLL fusion protein that activates Hox expression had no effect on histone methylation, suggesting a distinct mechanism for gene regulation by MLL and MLL fusion proteins.